Priestly Politics A Political Theology of Priestly Cultic Instructions - Peres, Caio (2025)
According to some scholarly consensus, the Priestly writings advance privilege and power for a group of established priests. From a political perspective, representatives of this consensus see in the Priestly writings the promotion of a centralized sociopolitical order, with priests holding political control over the Achaemenid province of Yehud, or at least attempting to do so. This article analyses two important concepts used in this characterization: hegemony and theocracy. From a more precise definition of hegemony, as found in Antonio Gramsci’s work, and theocracy, as coined by Flavius Josephus, this article shows that Priestly cultic instructions align well with the utopian and democratizing ideals that serve as a critique of every form of centralized systems of power.
Keywords: and Utopia; Theocracy; Hegemony; Ritual; Politics